2014
DOI: 10.2754/avb201483040295
|View full text |Cite
|
Sign up to set email alerts
|

Structural and ultrastructural study of the rabbit kidney exposed to carbamate insecticide

Abstract: The aim of the present study was to determine the influence of orally administered insecticide bendiocarb on the structure and ultrastructure of the kidney parenchyma in rabbits. Bendiocarb in the form of capsules (96% Bendiocarb, Bayer), at a dose of 5 mg/kg of body weight was fed daily for 3 days. After sampling, kidney sections of experimental and control animals were evaluated. Under a light and electron microscope the diffuse degenerative changes in kidney cortex and medulla were noted. Light microscopy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Bendiocarb was shown to alter homeostasis (Capcarova et al 2010;Mojzisova et al 2012) and induce morphological changes in different organs such as the thymus, kidneys, and liver (Flesarova et al 2007;Almášiová et al 2014;Holovska et al 2014). In agreement with previously published studies, it can be concluded that bendiocarb adversely affected the structure of rabbit tissues and organs.…”
Section: Discussionmentioning
confidence: 99%
“…Bendiocarb was shown to alter homeostasis (Capcarova et al 2010;Mojzisova et al 2012) and induce morphological changes in different organs such as the thymus, kidneys, and liver (Flesarova et al 2007;Almášiová et al 2014;Holovska et al 2014). In agreement with previously published studies, it can be concluded that bendiocarb adversely affected the structure of rabbit tissues and organs.…”
Section: Discussionmentioning
confidence: 99%
“…such as mitochondrial swelling and shortening of basal infoldings within proximal and distal tubules. Moreover, within Henle's loop, vacuolized cytoplasm was noticed and tubular sections revealed cellular detachment between the adjacent epithelial cells and rare necrotizing epithelial cells [26]. Kidney function in bendiocarb-treated rats was also compromised and was characterized as a disruption of antioxidative barrier (CAT, SOD, GPx) together with an increased level of malondialdehyde, creatine, urea, and uric acid.…”
Section: Histopathological Findingsmentioning
confidence: 99%
“…The animals developed convulsions and died within 30 minutes to one hour after ingestion of bendiocarb-soaked pieces of bread [25]. Acute bendiocarb intoxication causes tachycardia, pupil dilation, muscle contraction, excessive salivation, nausea, vomiting, as well as ataxia, seizures and coma [26,27,28]. The symptoms after intoxication include paralysis of muscles of the respiratory system with intense constriction of the pulmonary alveolus [20].…”
Section: Introductionmentioning
confidence: 99%